1990
DOI: 10.1507/endocrj1954.37.79
|View full text |Cite
|
Sign up to set email alerts
|

Silent Thyroiditis following Rubella.

Abstract: A 40-year-old housewife was referred to our hospital for evaluation of a thyrotoxic state. A month after rubella infection, she developed heat intolerance. Physical examination revealed a hard and non-tender goiter with no signs or symptoms of inflammation. Free thyroid hormones were high and TSH was undetectable. 123I-thyroidal uptake was suppressed. Antithyroglobulin and anti-microsomal antibodies were negative throughout the course. A serologic study revealed high levels of anti-rubella antibodies. After a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…In 1990, de Bruin et al [12] reported the presence of atypical subacute thyroiditis, which developed in 12 patients, including two family members in the same period (July-September). In both reports, flulike symptoms and liver dysfunction were observed in most of the patients, suggesting that viral infection might be a cause of thyrotoxicosis [8][9][10]. However, no evidence of a viral infection was obtained in these studies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In 1990, de Bruin et al [12] reported the presence of atypical subacute thyroiditis, which developed in 12 patients, including two family members in the same period (July-September). In both reports, flulike symptoms and liver dysfunction were observed in most of the patients, suggesting that viral infection might be a cause of thyrotoxicosis [8][9][10]. However, no evidence of a viral infection was obtained in these studies.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is suggested that iodine intake and various cytokines can initiate silent thyroiditis [3]. In addition, silent thyroiditis can also develop in patients after the cessation of steroid treatment for rheumatoid arthritis [4], after adrenalectomy in patients with Cushing's syndrome [5,6], after the administration of gonadotropin-releasing hormone analogues [7], and after viral infections [8][9][10]. However, the outbreak of silent thyroiditis (or atypical thyroiditis) has been indicated in few reports [11,12] Here, we report the cases of two brothers and their mother who developed silent thyroiditis in spring.…”
mentioning
confidence: 99%
“…An environmental toxic insult has been proposed in endocrine autoimmune processes as a trigger event for the disease in genetically susceptible individuals (Toni010 et al,, 1980;Nakamura et al,, 1990;Toussaint-Demylle et al, 1990;Sundick et al, 1992;Cavallo et al, 1992). How may this affect adhesion molecules?…”
Section: Lymphocyte Inflltratlon and Types Of Adheslon In Autoimmune mentioning
confidence: 99%
“…Die Patienten haben keine lokalen Beschwerden, insbesondere keine Schmerzen. Auffallend diskrepant sind häufig Höhe der Schilddrüsenhormonkonzentrationen und geringe bis fehlende klinische Beschwerden einer Hyperthyreose[12,32,33]. der Sonografie Das sonografische Bild ist variabel.…”
unclassified